Biochemical changes and development of soybean with use of pelletized organomineral fertilizer containing sewage sludge and filter cake (Acta Scientiarum. Agronomy, 2020)
Filter cake has been one of the most widely used waste products as a source of organic matter in the production of biofertilizers. However, sanitized sewage sludge is a recommended alternative for agricultural use because of environmental issues. Studies that examine the use of this particular class of fertilizer are needed. The objective of this work was to evaluate the efficiency of sewage sludge and filter cake as sources of organic matter in the composition of pelletized biofertilizers for soybean production. The experimental design was a randomized block design in a 2 x 4 + 2 factorial, which includes two sources of organic matter (sanitized sewage sludge and filter cake) and four levels of nitrogen (50, 75, 100, and 125%) relative to the recommended dose of phosphorus pentoxide compared with the mineral fertilizer. The use of organomineral fertilizer with the formulation of 75% sewage sludge showed greater growth for aerial plant parts. Biofertilizers formulated with sewage sludge and filter cake can replace mineral fertilizer and increase soybean growth. Quantitative changes in peroxidase, catalase and urease activity, as well as lipid peroxidation, were observed following the use of biofertilizers.